(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article provides recommendations for the university to provide understanding and skills on the use of innovative technologies in the "Education of competence of future teachers of computer science." Based on these recommendations, the role of information technology in educating the competence of a future computer science teacher is highlighted.